Hemoperitoneo secundario a tumor maligno de la vaina del nervio periférico en hígado - Chávez-Sánchez, SA (2024)
Malignant peripheral nerve sheath tumors are frequently associated with neurofibromatosis type 1. They are usually located in the extremities or in the axial area. Its visceral location is very rare and its hepatic origin is infrequent. They tend to be aggressive with a poor response to chemotherapy and radiotherapy, so surgical management is the best treatment option. We present the case of a young man with neurofibromatosis type 1, who presented with hemoperitoneum as a complication of a malignant tumor of the peripheral nerve sheath located in the liver.